A cross-sectional study exploring the perception of exercise oncology in the Italian population - Borsati, Anita; Giannarelli, Diana; Pase, Giampaolo; Ciurnelli, Christian; Toniolo, Linda; Trestini, Ilaria; Tregnago, Daniela; Belluomini, Lorenzo; Sposito, Marco; Insolda, Jessica; Milella, Michele; Schena, Federico; et al. (Frontiers in Oncology, 2025)
IntroductionWe aim to examine the population’s perception of physical exercise in patients with cancer.Materials and methodsAn anonymous survey was conducted to reach a sample of Italian adults. The questionnaire investigated sociodemographic factors, physical exercise levels, and perceptions about the importance, benefits, and safety of exercise, the support from oncologists and family/friends, as well as the capability and ease of patients of exercise.ResultsOverall, 838 persons participated in this survey. The majority of respondents agree that exercise is important (60.5%) and beneficial (61.5%) for patients with cancer during anticancer treatments, whereas 40.2% believed in its safety. Forty-two percent and 51.9% of participants expressed a positive opinion regarding the advice of oncologists and the encouragement of family/friends to exercise, respectively. Only 27.2% of respondents feel that patients are capable of exercising, and 9.0% agree that it is easy for them.ConclusionAlthough the population has a favorable perception of the importance and benefits of physical exercise, they do not still believe that patients are capable of performing it. Increasing awareness of the feasibility of a physical exercise intervention in the context of cancer is crucial to supporting patients.